2020
DOI: 10.1111/1759-7714.13486
|View full text |Cite
|
Sign up to set email alerts
|

High expression of KITLG is a new hallmark activating the MAPK pathway in type A and AB thymoma

Abstract: BackgroundKIT proto‐oncogene ligand (KITLG) is a pleiotropic factor which is found in diverse cancers and is involved in cell proliferation, differentiation, and survival. However, the value of KITLG in thymoma remains unclear.MethodsA total of 121 thymoma samples from The Cancer Genome Atlas Thymoma (TCGA‐THYM) dataset were used to analyze KITLG related genome‐wide expression profiles, and microRNA profiles and methylation alterations and a GEO dataset‐GSE29695, including 37 samples was used as verification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…ERK 1/2 is also an effective target for anticancer [ 25 ]. Studies have shown that MAPK signal and ERK 1/2 were significantly activated in thymoma [ 26 ]. TGF- β inhibited apoptosis and had reduced expression of IFN- γ in effector cell, a key mediator of antitumor immunity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERK 1/2 is also an effective target for anticancer [ 25 ]. Studies have shown that MAPK signal and ERK 1/2 were significantly activated in thymoma [ 26 ]. TGF- β inhibited apoptosis and had reduced expression of IFN- γ in effector cell, a key mediator of antitumor immunity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Elevated expression of KITLG has been associated with the pathological advancement of various malignancies, such as neurofibromatosis [21], glioma, and papillary thyroid carcinoma [14]. Furthermore, KITLG is now considered characteristic of WHO AB thymoma, potentially signifying a novel marker for differentiating WHO AB thymoma from other thymic tumors [22]. Recent investigations suggest that KITLG inhibits cancer through the induction and Amplification of multiple signaling pathways [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, DNA methylation levels seem to significantly correlate with overall and relapse-free survival in patients with TEN, thus representing a significant prognostic factor. All in all, both non-coding RNAs and DNA methylation levels could be regarded as potential epigenetic biomarkers in terms of accurate patient stratification in low versus high risk TEN, effective recurrence probability prediction and, most importantly, overall patient survival, with a great number of studies incorporating hundreds of samples from datasets, such as the TCGA, and providing reliable and reproducible data that prove the role of epigenetic modifications in TEN pathogenesis and prognosis [ 31 , 36 , 39 , 60 ]. Interestingly, HDACIs seem to represent promising epigenetic therapeutic agents with potent antitumor effects in TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the positive correlation between promoter DNA methylation and GAD1 expression in TEN was attributed to the inhibition of a Polycomb repressive complex 2 (PRC2) by the methylation of CCCTC-binding factor (CTCF) −3, with H3K27me3 levels markedly reduced at the GAD1 promoter. Through multiomic analysis of the TCGA, Yang et al reported that KIT proto-oncogene ligand (KITLG) represents a new hallmark of type A and AB thymomas by inducing aberrant alterations of mRNA, miRNA and DNA methylation [ 60 ].…”
Section: Alterations Of Dna Methylation In Tensmentioning
confidence: 99%